A fiber-shaped aqueous lithium ion battery with high power density. Issue 23 (26th May 2016) - Zhang, Ye; Wang, Yuhang; Wang, Lie; Lo, Chieh-Min; Zhao, Yang; Jiao, Yiding; Zheng, Gengfeng; Peng, Huisheng
Abstract : A fiber-shaped aqueous lithium ion battery is developed with ultrafast charge–discharge rates and high power density in addition to high energy density. Abstract : A new fiber-shaped aqueous lithium ion battery is developed using a polyimide/carbon nanotube hybrid fiber as the anode and LiMn2 O4 /carbon nanotube hybrid fiber as the cathode. This battery outputs a power density of 10 217.74 W kg −1, which exceeds that of most supercapacitors, and an energy density of 48.93 W h kg −1, which equals that of thin-film lithium ion batteries. The safety issue generated by flammable organic electrolytes is fundamentally resolved by using an aqueous electrolyte. Compared with the conventional planar structure, the fiber shape also provides some unique and promising advantages, e.g., being three-dimensionally deformable. It can be also woven into a flexible power textile to satisfy a variety of new emerging fields, such as microelectronics and wearable electronics.